A Comparative Analysis Of Islamic Economic Thought: Abu Yusuf And M. Umer Chapra - Anisa, Lina Nur (Journal of Economic and Islamic Research, 2024)
This article discusses the Islamic economic thoughts of two prominent figures, Abu Yusuf and M. Umer Chapra, focusing on the main question of how their contributions in different historical contexts can provide insights for the development of Islamic economic theory. Abu Yusuf, a jurist from the Abbasid era, through his work Kitab al-Kharaj, laid the foundation of economic thought focusing on state financial administration, taxation, and social justice. In contrast, M. Umer Chapra, a contemporary economist, integrates Islamic economic principles with modern challenges such as globalization and financial instability, emphasizing the importance of moral values in economics. This research uses a qualitative method with a literature study approach to comparatively analyze the thoughts of these two figures. The main findings indicate that despite the differences in historical context, the thoughts of Abu Yusuf and Chapra complement each other in offering solutions to achieve social justice and economic stability. Abu Yusuf focuses more on technical and administrative aspects, while Chapra emphasizes ethical and moral values. This combination of classical and modern thought provides a strong foundation for the holistic and applicable development of Islamic economics in the contemporary era.